Effect of near normoglycaemia for two years on progression of early diabetic retinopathy, nephropathy, and neuropathy: the Oslo study. - Dahl-Jørgensen, K (1986)
Forty five insulin dependent diabetics were randomised to treatment with continuous subcutaneous insulin infusion (CSII), multiple insulin injections (five or six daily), or conventional twice daily insulin injections. Near normoglycaemia was obtained with CSII and multiple injections but not with conventional treatment (p less than 0.01). Hypoglycaemic coma was observed less frequently with CSII than with multiple injections and conventional treatment (p less than 0.001), but blood glucose concentrations below 2.5 mmol/l (45 mg/100 ml) were more common. After two years fewer retinal microaneurysms and haemorrhages had developed in the patients given CSII and multiple injections compared with those given conventional treatment, in whom the number had increased significantly (p less than 0.01). Motor nerve conduction velocity deteriorated in the patients given conventional treatment; in those given CSII it was unchanged during the first year but had improved after two years (p less than 0.01). Glomerular hyperfiltration was reduced with CSII, but no change occurred in urine albumin excretion rates. Long term near normoglycaemia may prevent the progression of early stages of late diabetic complications.